Feasibility/acceptability of an acceptance‐based therapy intervention for diverse adolescent girls with overweight/obesity - Michelle I. Cardel; Alexandra M. Lee; Xiaofei Chi; Faith Newsome; Darci R. Miller; Angelina Bernier; Lindsay Thompson; Matthew J. Gurka; David M. Janicke; Meghan L. Butryn (Wiley, 2021)
Abstract Background Behavioral obesity interventions using an acceptance‐based therapy (ABT) approach have demonstrated efficacy for adults, yet feasibility and acceptability of tailoring an ABT intervention for adolescents remains unknown. Objective This study assessed the feasibility and acceptability of an ABT healthy lifestyle intervention among diverse adolescent cisgender girls with overweight/obesity (OW/OB). Methods Adolescent cisgender girls aged 14-19 with a BMI of ≥85th percentile‐for‐sex‐and‐age were recruited for participation in a single‐arm feasibility study. The primary outcomes were recruitment and retention while the secondary outcome was change in BMI Z‐score over the 6‐month intervention. Exploratory outcomes included obesity‐related factors, health‐related behaviors, and psychological factors. Results Recruitment goals were achieved; 13 adolescents (>60% racial/ethnic minorities) participated in the intervention, and 11 completed the intervention (85% retention). In completers (n = 11), a mean decrease in BMI Z‐score of −0.15 (SD = 0.34, Cohen's d = −0.44) was observed. Improvements were also noted for change in percentage of 95th percentile (d = −0.35), percent body fat (d = −0.35), quality of life (d = 0.71), psychological flexibility (d = −0.86), and depression (d = −0.86). Conclusions These preliminary findings suggest an ABT healthy lifestyle intervention tailored for adolescent cisgender girls with OW/OB may be an acceptable treatment that could lead to improvements in BMI Z‐score, obesity‐related measures, and psychological outcomes.